Historical changes in thermoregulatory traits of alpine butterflies reveal complex ecological and evolutionary responses to recent climate change. Issue 1 (December 2016) - MacLean, Heidi; Kingsolver, Joel; Buckley, Lauren
Abstract Background Trait evolution and plasticity are expected to interactively influence responses to climate change, but rapid changes in and increased variability of temperature may limit evolutionary responses. We use historical specimens to document changes in the size and thermoregulatory traits of a montane butterfly, Colias meadii, in Colorado, USA over the past 60 years (1953–2012). We quantify forewing wing length, ventral wing melanin that increases solar absorption, and the length of thorax setae that reduces convective heat loss. Results The mean of all three traits has increased during this time period despite climate warming. Phenological shifts may have extended the active season earlier at low elevations and later at high elevations, increasing exposure to cool temperatures and selecting for increases in thermoregulatory traits. Fitness increases at higher elevations due to warming could also increase thermoregulatory traits. Warmer temperatures during pupal development and later flight dates in the season are associated with decreased wing melanin, indicating a role of phenotypic plasticity in historical trait changes. Conclusions Phenotypic shifts result from a complex interplay of ecological and evolutionary responses to climate change. Environmental variability within and across seasons can limit the evolutionary responses of populations to increasing mean temperatures during climate change.